PENGARUH PELATIHAN DAN PEMAHAMAN PSAK EMKM TERHADAP KUALITAS LAPORAN KEUNGAN UMKM DAERAH TANJUNG SELOR KALTARA - Ayem, Sri; Singan, Delvi (Invoice : Jurnal Ilmu Akuntansi, 2021)
This study aims to see the effect of training and understanding of PSAK EMKM on the quality of the financial statements of SMEs in the Tanjung Selor area. The type of research used is quantitative research. The population in this study are SMEs in the fields of Culinary, Fashion, Beauty, Creative Products and have carried out accounting activities in business activities and have attended training in preparing financial reports and Agribusiness. The sample in this study amounted to 100 SMEs with a percentage of 1). Culinary 43 SMEs 2). Fashion 22 SMEs 3). Beauty 17 SMEs 4). Creative Products 12 SMEs and 5). Agribusiness 6 SMEs. The source of this research data is primary data using research instruments in the form of questionnaires. The data collection method used is by distributing questionnaires directly and Google forms. This research uses multiple regression analysis method. This research uses multiple regression analysis method. For statistical analysis and regression models have been tested first in the classical assumption test. The results of the study stated that the partial test showed that the PSAK EMKM training did not have a positive effect on the quality of the financial statements of the Tanjung Selor MSMEs and the partial test also showed that the understanding of PSAK EMKM had a significant positive effect on the quality of the financial statements of SMEs in the Tanjung Selor area as well as stimulant testing.